Edukasi Perilaku Hidup Bersih dan Sehat Pada Siswa Sekolah Dasar Negeri 20 Kota Palembang - Putri, Anggy Utama; Rosadi, Erik; Harisandy, Alvian (Nanggroe: Jurnal Pengabdian Cendikia, 2024)
Improving health is an effort in national development to achieve awareness, willingness and ability to live healthily for every resident in realizing a level of public health. The implementation of health development is directed at increasing awareness, willingness and ability to live with PHBS in the family, school and community environment. This community service activity aims to provide education about PHBS to elementary school students at state elementary schools. The method of implementing the activity is education consisting of counseling, video screening, discussion and question and answer. Participants in educational activities are students of SDN 20 Palembang City. The material presented is washing hands with soap before and after eating, brushing teeth and doing community service with members of the school environment to create a healthy environment. This community service activity succeeded in increasing participants' knowledge and understanding of PHBS, resulting in an increase in knowledge. PHBS educational activities in schools can be continued in other areas as an effort to foster clean and healthy living behavior at an early age